Pembangunan Karakter Bangsa di Wilayah Perbatasan antar Negara Indonesia dengan Timor Leste - -, Sapriya (Jurnal Civicus, 2010)
Pembangunan Karakter Bangsa di Wilayah Perbatasan antar Negara Indonesia dengan Timor Leste